Development and Validation of a Photographic Method to Use for Dietary Assessment in School Settings - Olafsdottir, Anna S.; Hörnell, Agneta; Hedelin, Marlene; Waling, Maria; Gunnarsdottir, Ingibjorg; Olsson, Cecilia (PLOS ONE, 2016)
Objective To develop and validate a photographic method aimed at making assessment of dietary intake in school canteens non-obstrusive, practical and feasible. Methods The study was conducted in two elementary schools representing two different school canteen systems; main dish being served by canteen staff (Iceland), and complete self-serving (Sweden). Food items in serving and leftovers were weighed and photographed. Trained researchers estimated weights of food items by viewing the photographs and comparing them with pictures of half and full reference portions with known weights. Plates of servings and leftovers from 48 children during five school days (n = 448 plates) and a total of 5967 food items were estimated. The researchers' estimates were then compared with the true weight of the foods and the energy content calculated. Results Weighed and estimated amounts correlated across meals both in grams and as total energy (0.853-0.977, p<0.001). The agreement between estimated energy content in school meals was close to the true measurement from weighed records; on average 4-19 kcal below true values. Organisation of meal service impacted the efficacy of the method as seen in the difference between countries; with Iceland (served by canteen staff) having higher rate of acceptable estimates than Sweden (self-serving), being 95% vs 73% for total amount (g) in serving. Iceland more often had serving size between or above the half and full reference plates compared with Sweden. Conclusions The photographic method provides acceptable estimates of food and energy intake in school canteens. However, greater accuracy can be expected when foods are served by canteen staff compared with self-serving.